The Process of Word Formation in English and Kurdish Languages: A Comparative Typological Study - Sardar Abdulmajid Abdullah; Waria Omer Amin (Zanco Journal of Humanity Sciences)
English and Kurdish are two morphologically different Indo-European languages. The first is the most analytic language among all of the European languages, while the second is an agglutinative, incorporating language. The paper concerns itself only with the standard dialects of the two languages, which are hypothesized to be different in the process of forming word. In this paper, an attempt is made to identify how many word-formation patterns occur in each language? Then, the paper aims at examining and contrasting where does English and Kurdish word formation resemble morphologically? And where do they differ? For this study, the data have been collected from various English and Kurdish sources and re-analyzed with reference to word formation in the two languages.